The Comparison Between Students’ Writing Achievement In Private and State of Junior High School - Putri, Riska Maharani; Prihatin, Yoga; Yuvita (South Asian Journal of Social Sciences and Humanities, 2020)
The objectives of this Research Project are to find out the differences between students’ writing achievement in state and private of junior high school and to identify the motivating factors that influence the difference between students’ English learning. The research method used is MMR (Mixed Method Approach). There are 66 students as the sample, 33 students from state and private school. The researcher analysis data by using t-test and questionnaire. The sig. 2-tailed is 0,012 while the significant level is at 5% level significance, which is 0,05. It indicates that there is a difference between students’ writing achievement in state and private school because the significance 2-tailed is less than the significant level (0,012 < 0,05). After the researcher analyzed the t-test, the researcher analyzed the questionnaire. The questionnaire is divided into two, internal factors and external factors. About 59% state school respondents gives positive responses toward internal factors while there is 51% private school respondents gives positive responses toward external factors.